Religious Development Management In Forming Noble Character Principles Of The Prisoner - Nawawi Abdurrauf, Ahmad; Wasliman, Iim; Andriana Gaffar, M.; Anwar, Mustatul (International Journal of Educational Research & Social Sciences, 2022)
This paper writing is motivated by the decline in public morals and the consequences of violations of the law that damage the social life order. During the sentencing process, prisoners are still shrouded somemindsets such as ; Trying to get out of the Penitentiary, holding a grudge against other people, feeling dissatisfied with the court decision, feeling like a person who does not get recognition from the community, feelins of disappointment and hopelessness and still difficult to eliminate in everyday life and people worry about not accepting it. or think negatively after finishing the punishment. The study aimedto describe the management of religious development in forming the noble character of prisoner based on Islamic boarding schools through the At-Taubah Integrated Islamic Boarding School (LPK-PPTA). The specific objective is to find out the management of prisoner religious development through the approach of (1) Planning, (2) Implementation (3) Evaluation (4) Problems (5) Solutions (6) Impact. The research formulation is how to manage religious development to shape the character of noble prisoners (a case study at the At-Taubah Integrated Islamic Boarding School Religious Development Institute, Class II B Amuntai Penitentiary, Hulu Sungai Utara Regency, South Kalimantan Province). This research used a naturalistic qualitative research approach namely the situation and conditions at the research locationwithout manipulation with descriptive qualitative research methods. The results of this study was aninnovative model of the Islamic boarding school-based religious development program, namely religious psychosomatic psychotherapy through coaching management functions. In the implementation of the management and correctional institutions involving all elements, both internal and external, it obtained good result both in terms of religious understanding (tafaqquh fiddin), life skills (life skills) and noble character (good character), in shaping character. noble character of prisoners. It is recommended to continue to carry out religious guidance for prisoners to make prisoners having faith, knowledge and do good deeds.